PENGARUH JUMLAH UANG BEREDAR,TINGKAT SUKU BUNGA DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Asnawi Asnawi; Hafizatul Fitria (LPPM Universitas Malikussaleh – Indonesia, 2018)
The purpose of this study is to determine the effect of the money supply,interest rates, and inflation on economic growth in Indonesia. The dataanalysis method used is Multiple Linear Regression. The data used are timeseries data from 1999-2017 which were interpolated. The results partiallyshow that the money supply and inflation have a positive and significantinfluence on economic growth in Indonesia, while interest rates do not affecteconomic growth in Indonesia. Simultaneously the money supply, interestrates and inflation have a significant influence on economic growth inIndonesia